Pemikiran Ekonomi Islam Ibnu Khaldun: Sebuah Pendekatan Sosio Historis - Mohammad Ridwan; Abdul Ghofur; Rokhmadi Rokhmadi; Gama Pratama (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2023)
This study examines Ibn Khaldun's economic ideas from the perspective of a socio-historical approach. The economic concepts of Ibn Khaldun have been widely cited as references by scholars and academicians all around the world. This article's research approach is library research because it concentrates on the figure of someone who has contributed to science through his works, which have been used as references by future generations. Based on the findings and discussions of Ibn Khaldun's thoughts on Islamic economics, it is decided that Ibn Khaldun is one of the Islamic philosophers who focuses on Islamic economic knowledge, with his major work being the Al-Muqaddimah. According to Ibn Khaldun's socio-historical approach to Islamic economics 1) Economic motives come from humans' boundless needs, while the things that can satisfy those demands are quite restricted; 2) In the field of economics, gold and silver are employed as benchmarks, namely as a means of exchange and evaluating prices, as a value of effort; secondly, as a method of communication, such as foreign exchange; and thirdly, as a savings instrument in banks. 3) A prosperous country is defined not by the amount of money it has, but by its level of production and a favorable balance of payments; 4) The connection between social and economic phenomena characterizes the socio-historical approach, with economic phenomena playing a critical role in the evolution of culture and having a substantial impact on the existence and growth of the state (daulah).Keywords: Ibn Khaldun; Economic Thought; Socio-Historical ApproachAbstrakPenelitian ini membahas pemikiran ekonomi Islam Ibnu Khaldun yang ditinjau dari pendekatan sosio historis dimana pemikiran ibnu khaldun tentang ekonomi, ini cukup banyak dijadikan rujukan oleh para peneliti dan akademisi dunia. Metode penelitian yang digunakan dalam artikel ini menggunakan library research, karena yang dibahas adalah ketokohan seseorang yang telah berkontribusi dalam ilmu pengetahuan melalui karya-karyanya yang telah dijadikan referensi oleh generasi selanjutnya. Berdasarkan hasil dan pembahasan tentang pemikiran ibnu khaldun terkait kajian ekonomi Islam disimpulkan bahwa Ibnu Khaldun merupakan salah satu tokoh filsuf Islam yang konsen dalam keilmuan ekonomi Islam dengan karya monumentalnya adalah Al-Muqoddimah. Corak pemikiran Ibnu Khaldun tentang ekonomi Islam dengan pendekatan sosio historis diantaranya: 1) motif ekonomi timbul karena hasrat manusia yang tidak terbatas, sedangkan barang-barang yang akan memuaskan kebutuhannya itu sangat terbatas; 2) emas dan perak dijadikan tolok ukur dunia perekonomian, yakni pertama, menjadi alat penukar dan pengukur harga, sebagai nilai usaha; kedua, menjadi alat perhubungan, seperti deviezen; dan ketiga, menjadi alat simpanan di bank; 3) Negara yang kaya tidaklah diukur dari banyaknya uang yang dimilikinya tetapi ditentukan berdasarkan tingkat produksi dan neraca pembayaran positif; 4) Pendekatan sosio historis ditandai dengan adanya fenomena sosial dengan fenomena lainnya yang saling berkaitan dimana fenomena ekonomis, memainkan peran penting dalam perkembangan kebudayaan, dan mempunyai dampak yang besar atas eksistensi negara (daulah) dan perkembangannya.Kata kunci: Ibnu Khaldun; Pemikiran Ekonomi; Pendekatan Sosio Historis